2013
DOI: 10.1016/j.jpsychores.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

“Functional somatic syndromes, one or many?”: An answer by cluster analysis

Abstract: The finding of symptom specific patterns in clusters which could not be differentiated on overall symptom severity is in favor of the splitters' view. The finding that all other clusters could be discriminated on overall symptom severity and that the 2-cluster solution had the best fit is in favor of the lumpers' view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…The findings of symptom profiles with no/few symptoms and with multiple symptoms were comparable with previous findings, [9][10][11][12][13][14] while only two of the previous studies also found symptom profiles defined by specific symptoms. 11,12 However, the number and description of the profiles differed from our findings except for an MS/pain profile, 11,12 a GI profile, 11,12 and an MS + GI profile.…”
Section: Relation To Other Studiessupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of symptom profiles with no/few symptoms and with multiple symptoms were comparable with previous findings, [9][10][11][12][13][14] while only two of the previous studies also found symptom profiles defined by specific symptoms. 11,12 However, the number and description of the profiles differed from our findings except for an MS/pain profile, 11,12 a GI profile, 11,12 and an MS + GI profile.…”
Section: Relation To Other Studiessupporting
confidence: 90%
“…Moreover, all the previous studies focused on medically unexplained symptoms or functional disorders, hence symptoms viewed as medically explained were excluded in many of the studies. 10,11,13,14 Most of the previous studies were further clinical studies and thus based on a highly selected population, [9][10][11]13 which could result in fewer or biased profiles if transferred to the general population.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the SEPAHAN project, there is not separate questionnaire to assess somatic complaints, however, we found 31 common items among questions contained in SEPAHAN's questionnaires with the 47-items questionnaire used in the Lacourt et al's study 33 and the patient health questionnaire (PHQ), [34][35][36][37] as standard tools for the assessment of somatic complaints, and therefore we established a 31-item validated questionnaire. This was used to evaluate the frequency of somatic complaints.…”
Section: Assessment Of Somatizationmentioning
confidence: 99%